1993
DOI: 10.1159/000284796
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Associated with Kidney Transplantation

Abstract: Anxiety associated with kidney transplantation was examined in a sample of 16 recipients. The incidence of anxiety amounted to 68.8% (11/16 cases) and 81.3% (13/16 cases) within the pre- and postoperation periods, respectively. One case indicated severe anxiety and finally developed dysthymic disorder after transplantation. Another case showed alexithymic features, which were associated with poor self-control, and strong defense mechanisms such as denial before transplantation. Although it is important for lia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Our prior studies have shown that alexithymic persons have poor social supports with significant others such as family and friends or have a poor -social network (9) suggesting that poor social supports of alexithymic persons may be associated with the difficulty in communicating with others, closely related to a marked difficulty in identhing and describing emotions. The first finding of a poor relationship among the persons, projected on the Synthetic House-Tree-Person Drawing Test, may be associated with an alexithymia-related characteristic, which suggests ddficulty in communicating with others.…”
Section: Resultsmentioning
confidence: 99%
“…Our prior studies have shown that alexithymic persons have poor social supports with significant others such as family and friends or have a poor -social network (9) suggesting that poor social supports of alexithymic persons may be associated with the difficulty in communicating with others, closely related to a marked difficulty in identhing and describing emotions. The first finding of a poor relationship among the persons, projected on the Synthetic House-Tree-Person Drawing Test, may be associated with an alexithymia-related characteristic, which suggests ddficulty in communicating with others.…”
Section: Resultsmentioning
confidence: 99%